Thermosensitive and biodegradable PCL-based hydrogels: potential scaffolds for cartilage tissue engineering. Issue 5 (24th March 2023) - Valipour, Fereshteh; Valioğlu, Ferzane; Rahbarghazi, Reza; Navali, Amir Mohammad; Rashidi, Mohammad Reza; Davaran, Soodabeh
Abstract: Due to a lack of sufficient blood supply and unique physicochemical properties, the treatment of injured cartilage is laborious and needs an efficient strategy. Unfortunately, most of the current therapeutic approaches are, but not completely, unable to restore the function of injured cartilage. Tissue engineering-based modalities are an alternative option to reconstruct the injured tissue. Considering the unique structure and consistency of cartilage tissue (osteochondral junction), it is mandatory to apply distinct biomaterials with unique properties slightly different from scaffolds used for soft tissues. PCL is extensively used for the fabrication of fine therapeutic scaffolds to accelerate the restorative process. Thermosensitive PCL hydrogels with distinct chemical compositions have paved the way for sophisticated cartilage regeneration. This review aimed to collect recent findings regarding the application of PCL in hydrogels blended with natural, synthetic materials in the context of cartilage healing.